Therapeutic Potential of Luffa acutangula: A Review on Its Traditional Uses, Phytochemistry, Pharmacology and Toxicological Aspects - Shendge, Parshuram Nivrutti; Belemkar, Sateesh (Frontiers in Pharmacology, 2018)
Luffa acutangula (Cucurbitaceae), a perennial plant grows mainly in India, Southeast Asia, China, Japan, Egypt and other parts of Africa, it is widely used in the traditional Indian medicinal system to treat various health conditions. The plant has been used in jaundice, diabetes, hemorrhoids, dysentery, headache, ringworm infection and leprosy. More than 50 chemical compounds have been isolated from a plant which mainly comprises flavonoids, anthraquinones, proteins, fatty acids, saponin triterpene, volatile components & other phytoconstituents. Crude extract of plant & its isolated compounds possess broad pharmacological activities such as antidiabetic, hepatoprotective, antiulcer, anticancer, immunomodulatory, antihyperlipidemic, antioxidant, antimicrobial, CNS depressant, analgesic & anti-inflammatory. The toxicological evaluation in preclinical studies reported safety of the plant for human consumption, but comprehensive evaluation in clinical studies is required. However, further investigation is necessary for transformation of experience based treatment of plant into evidence based information. Evaluation of pharmacological activity with indicative biomarkers will help to reveal the mechanism of action of chemical constituents of plant extract. The data from preclinical studies recommends clinical evaluation of safety & efficacy of the plant. The current paper summarizes up-to-date information about a review of the traditional uses, phytochemistry, pharmacological activities and toxicology to highlight the future prospects of the plant.